Totaluppereyelidreconstructionwith temporal advancement-transpositionflap, combinedwithan oral mucosalgraft. Case report - Moreira, Agustina; Juri, Maximiliano (Cirugía del Uruguay, 2025)
Sebaceous carcinoma is a rare andpotentially aggressive glandular neoplasm, with the most common site of presentation being the upper eyelid. Its clinical manifestation can vary. The usual treatment involves conventional resection or Mohs micrographic surgery, followed by appropriate reconstruction.Objective: To describe the reconstructive technique for managing a total defect of the upper eyelid using an advancement and transposition flap from the temporal region, combined with an oral mucosa graft in a single surgical procedure. Material and Methods: A clinical case is presented of a patient with sebaceous carcinoma of the upper eyelid, who underwent tumor resection followed by reconstruction using a transposition and advancement flap from the temporal region, with an oral mucosa graft. Discussion and Conclusions: The described technique is an effective option for reconstructing extensive upper eyelid defects. Its main advantage lies in the dynamic reconstruction of the eyelid, with minimal morbidity at the donor site and a skin texture and color similar to that of the temporal region. Additionally, it is performed in a single surgical procedure, is technically simple, and is carried out within a single operative field.